Jurnal Pengabdian Penarapan Platform Pembelajaran Digital Baca Al-Qur’an Daring Di Pesantren Baiturrahman Ciparay - Haryana, KM. Syarif; Husniah, Hennie; Maryanche, Octavia; Jabar, Denis Aji M. (Jurnal Pengabdian Tri Bhakti, 2021)
Responding to the Covid-19 pandemic encourages people to change their daily ways of thinking and behaving of education becomes the front line to break the chain of spreading Covid-19. Therefore, the policy of the central and local governments is to change the old learning patterns online. On the other, schools are expected to make adjustments to the implementation of this PSBB. Including the school under the guidance of the Baiturrahman Ciparay Islamic Boarding School, the education system for all subjects is converted into online including Al-Quran reading subjects at the Baiturrahman Islamic boarding school which is the flagship required to adjust the learning system so that curriculum targets can be achieved. However, the online method used in this subject has different demands because teachers and students have to face each other in an interactive, realtime manner. The solution applied is to take advantage of several Information Technology facilities so that students and teachers can take advantage of cellphones or notebooks in their respective places and simultaneously access the Google class application (Brock, 2015) to access various learning resources from teachers and Google Meet for materials that require face-to-face advance directly supported by multi media means